Pengaruh Pertumbuhan Ekonomi, Indeks Pendidikan, dan Pengangguran Terhadap Ketimpangan Pendapatan Di Provinsi Aceh - Helnita Manik; Ahzura Nauradah; Puti Andiny (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to determine whether there is an influence of economic growth, education index and unemployment on income inequality in Aceh Province in the 2013-2022 period. This study uses a quantitative approach. The type of data used is secondary data sourced from the Central Statistics Agency (BPS) in the form of a time series (10 years). The research analysis method was carried out using multiple linear regression. The data obtained was then analyzed using the Eviews 10 tool. Based on the research results, it shows that economic growth has a negative and partially insignificant effect on income inequality in Aceh Province, the Education Index has a partially negative and insignificant effect on income inequality in Aceh Province, unemployment partially negative and insignificant effect on income inequality in Aceh Province.